Multiple ways for the same destination: bone regeneration - Seong-Gon Kim (SpringerOpen, 2022)
Abstract The regeneration of the bone is a challenging topic for maxillofacial plastic and reconstructive surgeons. For successful bone regeneration, timely providing of essential components is prerequisite. They are cellular components (osteoblasts, osteoclasts, and immune cells), extracellular matrix, and inorganic components (calcium and phosphate). Any deficient component can be provided from outside as a graft. Accordingly, there are many ways for successful bone regeneration. Selection of appropriate methods in an individualized situation is important.